Diversité floristique et valeur de la forêt sacrée Bokasso (Est de la Côte d’Ivoire) pour la conservation - Adou Yao; C.Y.; Kpangui; K.B.; Kouao; K.J.; Adou; L.M.D.; Vroh; B.T.A.; N’Guessan; K.E. (VertigO)
The forest region located in eastern Côte d’Ivoire has been marked by a range of anthropogenic activities that has resulted in its degradation. In this region, the sacred forests are now for some administrative districts like Transua, the few relics that are still intact from the forest that used to stretch as far as Ghana. One of them, called Bokassô has been the subject of a study whose objectives are : (1) the definition of its area by mapping the site forest cover, (2) its botanical inventory and (3) the determination of its conservation status. The results indicate that the forest covers an area of 54.9 ha. It is reach of 188 plant species grouped in 154 genera and 64 families. The floristic composition shows that it is a fragment of well-preserved semi-deciduous rainforest. This forest is home to 30 species of conservation concerns and must thus be considered as being of high conservation value. However, many human activities threat the integrity of the forest.